Archiving the Web Site of the Bulgarian National Radio - Our Digital Memory Accessible Tomorrow - Krandeva, Anelia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2015)
The paper describes some of the issues of web archiving. The preparing the web site of the Bulgarian National Radio for web archiving is discussed.
Keywords: Digital Radio Archive; Multimedia; Radio; Cultural Heritage; Databases; Web Archiving